Rancang Bangun Pengaduk pada Mesin Pengaduk Adonan untuk Meningkatkan Produktifitas Kerupuk pada UMKM Ashoy Fajriya di Desa Padangan Kabupaten Kediri - Rahmad, Hadi (Politeknik Negeri Malang, 2022)
UMKM Ashoy Fajriya crackers SMEs need more equipment to increase production. Because of manually production of the crackers SMEs. The Team of the State Polytechnic of Malang planed to increase production of Ashoy Fajriya crackers SMEs. Several steps have been taken to solve this problem, namely by making a machine model, calculating the dimensions of the stirrer by analys to the forces acting on the stirrer, simulation, and making components. After that the team has also repaired several components after testing on the stirrer. Furthermore, it has also provided explanations about the operation and maintenance of machines to partners. From the evaluation that has been carried out, there was an increasing in ability and is expected to be able to solve problems that exist in Partners.